Oxidative stress-based cytotoxicity of delphinidin and cyanidin in colon cancer cells. - Cvorovic, Jovana; Tramer, Federica; Granzotto, Marilena; Candussio, Luigi; Decorti, Giuliana; Passamonti, Sabina (Arch Biochem Biophys, 2010)
Colorectal cancer is the second most frequent cause of cancer death in the western world. Although the prognosis has improved after the introduction of newer anticancer drugs, the treatment of metastatic colorectal cancer still remains a challenge due to a high percentage of drug-resistant tumor forms. We aimed at testing whether anthocyanidins exerted cytotoxicity in primary (Caco-2) and metastatic (LoVo and LoVo/ADR) colorectal cancer cell lines. Both cyanidin and delphinidin, though neither pelargonidin nor malvidin, were cytotoxic in metastatic cells only. The cell line most sensitive to anthocyanidins was the drug-resistant LoVo/ADR. There, cellular ROS accumulation, inhibition of glutathione reductase, and depletion of glutathione could be observed. This suggests that anthocyanidins may be used as sensitizing agents in metastatic colorectal cancer therapy.
Keywords: Anthocyanins; Antioxidants; Apoptosis; Caco-2 Cells; Camptothecin; Cell Line, Tumor; Colonic Neoplasms; Drug Resistance, Neoplasm; Glutathione; Glutathione Reductase; Humans; Oxidants; Oxidative Stress